How Could Judges Ignore the Audi Et Alteram Partem Principle in a Criminal Case Trial? - Hidayat, Raihan Akbar; Hidayat, Beni; Kodio, Ahmed Hedieloum (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2023)
In a judge's decision, legal considerations aim to delve into the facts revealed at trials based on the audi et alteram partem principle, which must exist and become a foundation. The philosophy of the audi et alteram partem principle is essentially the values of justice and balance. In applying the audi et alteram partem principle in a criminal case, although the judges have judicial power, they should consider the evidence and facts that are not only submitted by the public Prosecutor but also have to consider the evidence and facts submitted by the defendant. In decision Number 123/Pid.B/2022/PN Yyk, the panel of examining judges rejected the explanation of the witness a de-charge  which was not based on a clear reason, so it was felt that the panel of judges examining the case did not consider the explanation of the witness which was mitigating for the defendant and violated the principle of audi et alteram. Therefore, this study aims to elaborate on how the judicial panel examined the case by applying the audi et alteram partem principle. To answer these legal issues, this study uses combined research methods of normative and empirical data with data collection methods by conducting interviews and literature reviews as well as using descriptive qualitative data analysis methods. The result of this study showed that the judicial panel examining case number 123/Pid.B/2022/PN Yyk did not consider the audi et alteram partem principle for the judgment because the judges were not balanced by only considering the prosecutor's explanation and rejecting the testimony of the defendant's witnesses and ignoring material truth of defendant's proof.